2016
DOI: 10.1098/rspb.2016.0825
|View full text |Cite
|
Sign up to set email alerts
|

Climate constrains lake community and ecosystem responses to introduced predators

Abstract: Human activities have resulted in rising temperatures and the introduction or extirpation of top predators worldwide. Both processes generate cascading impacts throughout food webs and can jeopardize important ecosystem services. We examined the impact of fish stocking on communities and ecosystems in California mountain lakes across an elevation (temperature and dissolved organic carbon) gradient to determine how trophic cascades and ecosystem function vary with climate. Here, we show that the impact of fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…Large zooplankton species are known to be more vulnerable to high temperatures and pollutants (Moore andFolt 1993, Symons andShurin 2016). Competition among zooplankton species is often size mediated, as numerous studies have demonstrated that large zooplankton species are stronger competitors and tend to competitively exclude smaller species from local communities (Brooks and Dodson 1965, Dodson 1974, Shurin 2001, Symons and Shurin 2016. The higher temperatures in more urbanized ponds and perhaps also other unmeasured anthropogenic pressures, such as pollution, could have acted as a filter and selected against larger species in our study system, thus resulting in significant pure effects of urbanization on body size and phylogenetic turnover ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Large zooplankton species are known to be more vulnerable to high temperatures and pollutants (Moore andFolt 1993, Symons andShurin 2016). Competition among zooplankton species is often size mediated, as numerous studies have demonstrated that large zooplankton species are stronger competitors and tend to competitively exclude smaller species from local communities (Brooks and Dodson 1965, Dodson 1974, Shurin 2001, Symons and Shurin 2016. The higher temperatures in more urbanized ponds and perhaps also other unmeasured anthropogenic pressures, such as pollution, could have acted as a filter and selected against larger species in our study system, thus resulting in significant pure effects of urbanization on body size and phylogenetic turnover ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Across our study region, lake catchments received the most precipitation during winter months (November-February; data not shown), when precipitation falls as snow. The relatively large proportions of community variation attributable to temperature, solar radiation, and precipitation underscore the vulnerability of mountain zooplankton communities to climate change, which may be compounded by climate-mediated changes to other more local environmental variables, such as land cover alteration or enhanced predation rates by exotic fishes (Messner et al 2013, Symons andShurin 2016). For instance, low winter snow accumulation may lead to reduced water levels or desiccation in smaller temporary ponds, while high rates of runoff from large snowpack may disrupt biota in mountain lakes (Girdner and Larson 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in temperature might directly affect zooplankton physiology or indirectly influence zooplankton through bottom–up effects. Often the effects of temperature cannot be disentangled from the effects of nutrients, as low elevation, warm, lakes in Sierra Nevada (CA) also have greater primary productivity as well as higher levels of detritus and dissolved organic carbon (Symons and Shurin ). Hence, the effect of lake temperature on size at maturity could be confounded or be a synergistic response to high temperature and food availability, which can potentially increase growth and/or egg production of zooplankton (Kvile et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Often the effects of temperature cannot be disentangled from the effects of nutrients, as low elevation, warm, lakes in Sierra Nevada (CA) also have greater primary productivity as well as higher levels of detritus and dissolved organic carbon (Symons and Shurin ). Hence, the effect of lake temperature on size at maturity could be confounded or be a synergistic response to high temperature and food availability, which can potentially increase growth and/or egg production of zooplankton (Kvile et al ). In our common‐garden experiment, food availability was controlled, leaving only the effect of temperature, thus indicating that differences in size at maturity are physiological adaptations in response to temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation